A role of active brown adipose tissue in cancer cachexia? - Emiel Beijer; Janna Schoenmakers; Guy Vijgen; Fons Kessels; Anne-Marie Dingemans; Patrick Schrauwen; Miel Wouters; Wouter van Marken Lichtenbelt; Jaap Teule; Boudewijn Brans (Oncology Reviews, 2012)
Until a few years ago, adult humans were not thought to have brown adipose tissue (BAT). Now, this is a rapidly evolving field of research with perspectives in metabolic syndromes such as obesity and new therapies targeting its bio-energetic pathways. White, brown and socalled brite adipose fat seem to be able to trans-differentiate into each other, emphasizing the dynamic nature of fat tissue for metabolism. Human and animal data in cancer cachexia to date provide some evidence for BAT activation, but its quantitative impact on energy expenditure and weight loss is controversial. Prospective clinical studies can address the potential role of BAT in cancer cachexia using 18F-fluorodeoxyglucose positron emission tomography-computed tomography scanning, with careful consideration of co-factors such as diet, exposure to the cold, physical activity and body mass index, that all seem to act on BAT recruitment and activity.